Personalization of Adaptive Learning Modules: Differential Impact Analysis Based on Students' Prior Knowledge Profiles and Self-Regulated Learning Levels - Sudi Dul Aji; Nurul Ain; Akhmad Zaini; Hestiningtyas Yuli Pratiwi; Kadek Dwi Hendratma Gunawan; Salsabila Kholifahtun Nisa’; Muhammad Nur Hudha (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to identify student learner profiles based on a combination of prior knowledge and Self-Regulated Learning (SRL) levels and to analyze the differential impact of an adaptive learning module on knowledge and SRL improvement in each profile. Using a mixed-methods explanatory sequential design, 92 undergraduate physics education students were selected through purposive sampling. K-Means cluster analysis was applied to form learner profiles, followed by a six-week pre–post intervention and qualitative interviews. The results identified three learner profiles (Proficient-Autonomous Learner, Resilient-Developing Learner, and Proficient-Fragile Achiever). The result showed that the adaptive module significantly improved Results showed significant knowledge gains across profiles, while SRL improvements differed significantly. The Proficient–Fragile Achiever group demonstrated the largest SRL gain (p < .001; large effect size, d > 0.80), associated with more frequent scaffolding support. In conclusion, the effectiveness of adaptive modules is highly dependent on learner profiles, with the most significant benefits in their ability to provide external support for building self-regulation skills. These findings imply that learning technology design should incorporate SRL as a key variable for personalization, and institutions can utilize these platforms as intervention tools for students with weak learning independence.